Pure titanium fabrication with spatter-less selective laser melting in vacuum - Yuji Sato (Elsevier, 2021)
Selective laser melting (SLM), which is an additive manufacturing technology, is attractive due to its ability to freely form shapes. SLM forms a 3D material by building it layer-by-layer from a metal powder. However, some issues have yet to be resolved, including dimensional accuracy, surface finish, processing time, and mechanical properties such as surface roughness, hardness, and crystal orientation. We demonstrate that pure titanium (Ti), which is clinically used for artificial bone and hard tissue implants because it is lightweight and biocompatible, can be fabricated by the SLM process in vacuum to develop a spatter-less process. The amount of spatter was dependent on the laser scanning rate; at 10 mm/s and an output power of 200 W, the spatter was minimized so that the surface roughness was reduced to 4.2 µm from 50 µm with a laser scanning rate of 50 mm/s. Defects such as pores, voids and delamination were found to be caused with an increase in the amount of spatter.